Heart attack – it’s not the end... – outpatient management after acute coronary syndrome - Główczyńska, Renata (Przewodnik Lekarza/Guide for GPs, 2007)
Management in patients after acute coronary syndromes (ACS) is a challenge to every physician. The aim of the treatment in patients after ACS is based on two parts: improvement of prognosis by prevention of myocardial infarctions and deaths and reduction of symptoms of coronary artery disease. Treatment concentrates on pharmacological and non-pharmacological management.